Can forgetting be constructive? - The hermeneutics of memory, forgiveness and reconciliation - Hołda, Małgorzata (Studia Philosophiae Christianae, 2019)
In his hermeneutics of memory, Ricoeur points to the dialectic character of the interrelation between remembering and forgetting. He abandons an understanding of forgetting as limited only to oblivion, or to deletion in the Bergsonian use of the term. He supplants the negativity of forgetting by the productivity of disremembering, and stretches forgetting to its reserve, to the dynamic unveiling of the details of past events, with varied degrees of truthfulness and accuracy. This article attempts to demonstrate that the positivity of forgetting in the context of reconciliation is a tangible possibility. Forgetting is viewed here as a positive, constructive faculty, which influences the future, makes it possible to create and shape it, and is opposed to a slavish adherence to memory anchored wholly in the past. The totality of the anchorage in the past results in an exclusive focus on remembering, and causes the impasse of being entrapped in a disconsolate past. We ascertain that forgetting is not a failure but rather a productive possibility, either self- -creative or purgative, to educate oneself and the Other towards a more promising future.